Shaping Students’ Responsibility Character: Evidence from PIK-R Extracurricular Activities - Satria Ihza Rizqullah; Eni Rahmawati (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2026)
This study aims to analyze the role of PIK-R extracurricular activities in shaping students’ sense of responsibility at one of SMA Negeri in Tegal. It employs a qualitative approach with a case study design to examine how the value of responsibility is internalized, practiced, and manifested within the context of extracurricular activities. The research subjects consisted of four informants selected through purposive sampling, namely the advisor, the chairperson, and two active PIK-R members. Data were collected through participant observation, semi-structured interviews, and documentation and were analyzed using an interactive model. The results of the study indicate that the character of responsibility develops through an integrated process that includes the internalization of values, participation in organizational practices, behavioral manifestations, role modeling, and support from a structured program. The value of responsibility is formed through habituation, active involvement in tasks, and direct experiential learning, while role modeling by the advisor and the chairperson strengthens the process of value internalization. This study also identifies limitations in the aspects of evaluation and reflection, which are still not systematically implemented. These findings imply that the integration of structured reflection and evaluation mechanisms is essential to optimize character development outcomes. Practically, this study suggests that schools and extracurricular advisors should design more systematic reflective activities and assessment strategies to strengthen students’ responsibility character.